Long-term adaptation of lymphoma cell lines to hypoxia is mediated by diverse molecular mechanisms that are targetable with specific inhibitors - Daumova, Lenka; Manakov, Dmitry; Petrak, Jiri; Sovilj, Dana; Behounek, Matej; Andera, Ladislav; Vit, Ondrej; Souckova, Olga; Havranek, Ondrej; Dolnikova, Alex; Renesova, Nicol; Tuskova, Liliana; et al. (Cell death discovery, 2025)
A large body of evidence suggests that hypoxia drives aggressive molecular features of malignant cells irrespective of cancer type. Non-Hodgkin lymphomas (NHL) are the most common hematologic malignancies characterized by frequent involvement of diverse hypoxic microenvironments. We studied the impact of long-term deep hypoxia (1% O2) on the biology of lymphoma cells. Only 2 out of 6 tested cell lines (Ramos, and HBL2) survived ≥ 4 weeks under hypoxia. The hypoxia-adapted (HA)b Ramos and HBL2 cells had a decreased proliferation rate accompanied by significant suppression of both oxidative phosphorylation and glycolytic pathways. Transcriptome and proteome analyses revealed marked downregulation of genes and proteins of the mitochondrial respiration complexes I and IV, and mitochondrial ribosomal proteins. Despite the observed suppression of glycolysis, the proteome analysis of both HA cell lines showed upregulation of several proteins involved in the regulation of glucose utilization including the active catalytic component of prolyl-4-hydroxylase P4HA1, an important druggable oncogene. HA cell lines demonstrated increased transcription of key regulators of auto-/mitophagy, e.g., neuritin, BCL2 interacting protein 3 (BNIP3), BNIP3-like protein, and BNIP3 pseudogene. Adaptation to hypoxia was further associated with deregulation of apoptosis, namely upregulation of BCL2L1/BCL-XL, overexpression of BCL2L11/BIM, increased binding of BIM to BCL-XL, and significantly increased sensitivity of both HA cell lines to A1155463, a BCL-XL inhibitor. Finally, in both HA cell lines AKT kinase was hyperphosphorylated and the cells showed increased sensitivity to copanlisib, a pan-PI3K inhibitor. In conclusion, our data report on several shared mechanisms of lymphoma cell adaptation to long-term hypoxia including: 1. Upregulation of proteins responsible for glucose utilization, 2. Degradation of mitochondrial proteins for potential mitochondrial recycling (by mitophagy), and 3. Increased dependence on BCL-XL and PI3K-AKT signaling for survival. In translation, inhibition of glycolysis, BCL-XL, or PI3K-AKT cascade may result in targeted elimination of HA lymphoma cells.